The Difference of FEV1/FVC Ratio Between Junior High School Students Living in Highland and Lowland - Fauzi, Fajar Shodiq Irsyad; Jusup, Sinu Andhi; ., Martini (Nexus Biomedika, 2015)
Background: Geographically, highland is a place that has an altitude more than 500 meters above sea level. Highland has some environmental characteristic differences, thus people need an adaptation process that affects their multiple organ system. One of the systems affected is respiration system. FVC (forced vital capacity) is the total volume of air that can be forcibly exhaled in one breath. FEV1 (forced expiratory volume 1st) is the volume of air that can be exhaled in the first forced expiration. FEV1/FVC ratio is one of the lung function parameters that can describe condition of the airway. This research aimed to analyze the difference of FEV1/FVC ratio between junior high school students living in highland and lowland. Method: This research was a cross-sectional observational analytic. Samples of this research were 9th grade students of Junior High School (SMP) Amal Mulya Tawangmangu, Karanganyar and Junior High School (SMP) Negeri 2 Kretek, Bantul.Â The data were collected by using non-random purposive quota sampling with inclusion and exclusion criteria that had been specified. FEV1/FVC ratio data were measured by Minato Autospiro AS300 Spirometer, while the Respiratory rate and the chest circumference index were collected as supporting data. The data were analysis with the Kolmogorov-Smirnov test, the Mann-Whitney test and the independent t-test. Result: The Kolmogorov-Smirnov test showed that the FEV1/FVC ratio were not normally distributed. Mean of FEV1/FVC ratio of junior high school students living in highland was 98.52Â±2.15 whereas mean of its living in lowland was 97.65Â±3.30. The result of the Mann-Whitney comparative test showed p = 0.959 (p>0.05). Conclusion: There is no significant difference of FEV1/FVC ratio between junior high school students living in highland and lowland. Keywords: FEV1/FVC ratio, highland, lowland, lung function, spirometer